Understanding factors influencing User Experience of interactive systems: A literature review - Ahsanullah, (Asian Research Publishing Network, 2015)
In recent years, the notion of User Experience (UX) has gained a greater attention among HCI researchers in academia and industry. Due to its importance, several frameworks and models have been proposed to design and assess UX of interactive systems. These models guide to improve the design and help to determine the quality of interactive systems, products and services. UX is highly subjective, dynamic, and context dependent; it evolves during the interaction with the system. Different factors collectively influence UX and present a challenging task to define, model, measure and validate it. The less attention is paid to understand and underline these factors; this paper is an attempt to understand and underline the core UX factors based on literature review. These factors make UX more complex, diverse and vague in nature. It is recommended to incorporate the management aspect in UX process that may help to overwhelming the issues of complexity, diversity and vagueness.